EU, Russia and the reshaping of the post-Soviet economic space: an international trade analysis. - Maria Stella Chiaruttini (European Regional Science Association (ERSA), 2014)
The last decades have witnessed the rise of a new wave of economic regionalism, the most remarkable example of which is the European Union. Regional economic integration is generally interpreted either as an attempt to resist the centrifugal forces of globalisation by strenghtening economic ties within a narrower area or as an intermediate step towards deeper integration at worldwide level. The ongoing evolution of the European Union makes it difficult to ascertain its real nature. At present, however, notwithstanding recent enlargements, the intra-EU trade share on total EU exchanges is declining while the dependence of the area on external markets, among which Russia, is increasing. The study of the economic and geopolitic relations between EU and Russia is rather intricate due to the overlapping of several scenarios. On the one hand there are the growing interconnections between EU and Russia which have led to envisage the creation of a Common Economic Space or even of a free trade zone, moving towards a pan-Eurasian economic block bridging the historic East-West divide. On the other hand there is the progressive penetration of the EU into the former Soviet space parallel to Russia's attempt to maintain its leading role in the East. From this perspective the EU may appear as a Western hegemon seeking to englobe an evergrowing periphery at the expense of a marginalised Russia. In this light the launching of the Customs Union of Belarus, Kazakhstan and Russia but especially the project of the Eurasian Economic Union would represent a Russia-inspired version of the EU in direct competition with the latter for the control of the post-Soviet space. Thus, instead of fading borders there would be two rival projects of regional integration. This interpretation is consistent with a view of regionalism as resistance not just to globalisation but specifically to EU's expansion. According to a different perspective, however, Eurasian integration might be seen as an intermediate stage alternative to an inclusion into the EU economic space. Leaving aside political considerations, the inclusion of a country into a regional block should be in principle motivated by a preexisting, although partial, de facto economic integration, to be furthered after formal accession. This contribution aims at providing an overview on the trade links between EU, Russia and the other transition economies, offering a background for the debate on the reshaping of the post-Soviet space. The questions to answer are: to what extent Russian and EU markets are interdependent; how far trade integration of the new accession countries inside the EU has progressed in comparison to that with Russia; and finally to which of the two regional blocks, the European or the Eurasian Economic Union, post-Soviet countries appear to be closer trade partners.
Keywords: F14; F15; P2; 330; economic regionalism; European Union; post-Soviet states; transition economies